2009
DOI: 10.1007/s10120-008-0465-8
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy with 5-FU or regimens including oral fluoropyrimidine for curable gastric cancer

Abstract: tration of 45-Gy radiotherapy and fi ve courses of chemotherapy consisting of 5-fl uorouracil (5-FU) and leucovorin. Postoperative adjuvant chemoradiotherapy (CRT) showed a statistically signifi cant improvement of relapse-free survival (RFS) and overall survival (OS) for patients with gastric cancer undergoing curative surgery, compared with surgery alone as control. The 3-year OS after CRT was 50%, while that of the surgeryalone group was 41% (hazard ratio [HR], 1.35; 95% confi dence interval [CI], 1.09-1.66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Finally, perioperative CT is under investigation, and the excellent Japanese results with S-1, to our knowledge, have not been reproduced in the West. 8,29 The role of RT alone as adjuvant treatment was reported in a randomized trial 30 in which 145 patients received surgery alone, 138 were administered postoperative CT, and 153 were given postoperative RT. No survival differences were reported, but RT offered an advantage in terms of reduction in local recurrence (27% with surgery alone vs 10% with surgery and RT).…”
Section: Commentmentioning
confidence: 99%
“…Finally, perioperative CT is under investigation, and the excellent Japanese results with S-1, to our knowledge, have not been reproduced in the West. 8,29 The role of RT alone as adjuvant treatment was reported in a randomized trial 30 in which 145 patients received surgery alone, 138 were administered postoperative CT, and 153 were given postoperative RT. No survival differences were reported, but RT offered an advantage in terms of reduction in local recurrence (27% with surgery alone vs 10% with surgery and RT).…”
Section: Commentmentioning
confidence: 99%
“…For these patients, only one prospective non-randomized study demonstrated a gain of survival with adjuvant chemoradiotherapy [8]. The interpretation of this finding is limited by the retrospective analysis of the study and by conflicting results in the surgical group [9]. …”
Section: Introductionmentioning
confidence: 99%